543 Eating habits and nutritional status of women with musculo- 2 skeletal diseases (Balneo and PRM Research Journal, 2024)
Abstract: Different theories link chronic musculoskeletal pain with lifestyle components, including diet. However, nutritional assesment and optimization is not routinely in- cluded into the medical management of patients with muskuloskeletal diseases (MSKD). In this study we aimed to evaluate the diet and nutritional status of a group of women with MSKD and to assess the extent to which they comply with the general recommenda- tions for a healthy diet. The results showed that 97% of the subjects included were over- weight or obese, and the compliance to different general nutritional recommandations ranged between 3% to 57%. Furthermore, the quality of life of this patients measured through SF-36 questionnaire was severly affected and the reported pain intensity on nu- meric pain scale had a mean of 8 (±1.3) in our study group. Although there are currently no specific guidelines for the nutrition of patients with chronic pain, an important first step would be to guide these patients towards an increase in diet quality and a healthy lifestyle by adhering to general nutritional recommendations regarding healthy eating. Keywords: diet, nutritional status, musculoskeletal disease, chronic pain